Analyzing Students' and Lecturers' Prior Knowledge of Basic Physics Laboratory: Perspectives on Local Wisdom Integration, Critical Thinking, and Science Process Skills - Tri Ariani; Sri Purwaningsih; Bambang Hariyadi; Maison, Maison (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
This study aims to map the prior knowledge of students and lecturers regarding basic physics laboratory implementation, the integration of local wisdom, and the mastery of critical thinking and science process skills, in order to identify learning gaps that demand instructional innovation. Using a descriptive–exploratory method, the research involved 60 Physics Education students and 10 lecturers from Universitas PGRI Silampari through a validated questionnaire measuring four aspects: laboratory implementation, integration of local wisdom, critical thinking and science process skills, and learning constraints and expectations. Descriptive and quantitative analyses were conducted based on Likert scale criteria. The findings show that laboratory activities remain dominated by procedural “cookbook” practices with limited inquiry opportunities. Both students and lecturers acknowledge the value of integrating local wisdom to enhance conceptual understanding, yet limited facilities and the lack of contextual guidelines pose major obstacles. The study concludes that inquiry-based laboratory designs integrated with local wisdom are urgently required to shift practices from verification toward authentic scientific exploration. Theoretically, this research contributes to contextualized science education models, while practically offering a framework for lecturers and institutions to reform laboratory practices into more meaningful, culturally relevant, and skill-oriented learning experiences.